2021
DOI: 10.1007/s11606-021-07065-0
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Hospital-at-Home Among Stakeholders: a Meta-synthesis

Abstract: Background Hospital-at-home (HaH) provides acute healthcare in patients’ homes as an alternative to traditional hospital inpatient care. HaH has been shown to improve clinical outcomes, increase patient satisfaction, and reduce hospitalization costs. Despite its effectiveness, the uptake of HaH remains slow and little is known about factors that impact the quality and transferability of HaH. This review aimed to qualitatively synthesize existing literature to examine the perspectives of stakeholde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 56 publications
0
56
0
Order By: Relevance
“…(38) Facilitators at the organisational level related to supportive operational, regulatory and legal frameworks, co-ordination and integration of care, including with post-discharge care; and staff with strong clinical and communication skills. (15, 34, 38)…”
Section: Resultsmentioning
confidence: 99%
“…(38) Facilitators at the organisational level related to supportive operational, regulatory and legal frameworks, co-ordination and integration of care, including with post-discharge care; and staff with strong clinical and communication skills. (15, 34, 38)…”
Section: Resultsmentioning
confidence: 99%
“… 18 , 19 Additionally, HaH patients did not perceive a continuity gap unlike many patients who transition from the inpatient hospital setting to home. 20 …”
Section: Acute Hospitalization At Home During the Covid-19 Pandemicmentioning
confidence: 99%
“…Studies on current HaH have shown that family members and home caregivers play an important role in the successful outcome of HaH. 20 , 29 , 30 For patients of families with adverse SDOH, this might be particularly true. 20 , 30 A discussion with the patient’s family or others assisting in care is necessary to uncover concerns regarding their roles, skills, financial status, and general ability to provide valuable home assistance.…”
Section: The Possible Future Role Of Acute Home Hospitalization In Co...mentioning
confidence: 99%
See 2 more Smart Citations